2009
DOI: 10.1177/1368430208098777
|View full text |Cite
|
Sign up to set email alerts
|

How Perspective-Taking Helps and Hinders Group-Based Guilt as a Function of Group Identification

Abstract: In two studies we hypothesized that outgroup perspective-taking promotes group-based guilt among weakly identifi ed perpetrator group members, but hinders it among higher identifi ers. In Study 1, native Dutch participants (N = 153) confronted their group's past mistreatment of outgroups, while perspective-taking was manipulated. This manipulation signifi cantly increased guilt among lower identifi ers, but decreased guilt among higher identifi ers. In addition, guilt predicted positively participants' support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 118 publications
(79 citation statements)
references
References 43 publications
(111 reference statements)
4
72
0
1
Order By: Relevance
“…Because past research has found that ingroup identifi cation moderates the infl uence of deliberate perspective taking (Zebel et al, 2008), in the present study we also examined how it was related to spontaneous perspective taking. Further, we examined whether feelings of group-based anger were directly related to collective action.…”
Section: Studymentioning
confidence: 99%
See 4 more Smart Citations
“…Because past research has found that ingroup identifi cation moderates the infl uence of deliberate perspective taking (Zebel et al, 2008), in the present study we also examined how it was related to spontaneous perspective taking. Further, we examined whether feelings of group-based anger were directly related to collective action.…”
Section: Studymentioning
confidence: 99%
“…Specifi cally, as also proposed by Zebel et al (2008), the effects of outgroup perspective taking on group-based guilt and collective action may depend upon the extent to which majority group members are identifi ed with their ingroup. Engaging in outgroup perspective taking may entail negative thinking about the ingroup.…”
Section: The Possible Role Of Ingroup Identifi Cationmentioning
confidence: 99%
See 3 more Smart Citations